Accessing other people's technology - Nottenburg, Carol; Pardey, Philip G.; Wright, Brian D. (International Food Policy Research Institute, 2003)
Public and private nonprofit institutions worldwide engaged in agricultural research and biotechnology are increasingly active participants in intellectual property transactions, interacting with the for-profit sector and even spawning private entities of their own. Notably absent from the group of nonprofit insti-tutes seeking patent protection are the 16 centers of the Consultative Group on International Agriculture Research (CGIAR). Located primarily in developing countries, only a few centers have obtained patent protection for their inventions. Nonprofit research institutions are not in the business of selling products to con-sumers. If they are to realize a return on their investment, they must sell rights to their technologies to commercial entities or other research institutions rather than make them freely available. A nonprofit entity may, for example, exclusively license technology to a commercial partner, license the technology itself nonexclusively, or use the technology as the foundation for a spin-off company.